2022
DOI: 10.3390/su14084516
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable but Not Spontaneous: Co-Operatives and the Solidarity Funds in Italy

Abstract: This paper aims to highlight the role of solidarity funds in the development and support of national co-operative movements. Those are financial institutions specialized in supporting the start-up and growth of co-operatives. By adopting a case study approach, our analysis shows that solidarity funds emerged globally with similar objectives. Our international comparison focuses on Italy but includes France, the United Kingdom and Québec as a specific Canadian province with a French institutional environment. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…They were suffering from the results of the Industrial Revolution with low pay, unhealthy cities, and dangerous workplaces resulting in a cooperative existing through mutual self-help. A sense of mutual help has been observed also in other countries, such as Italy, where according to the Law 59 (1992) [40] all cooperatives must transfer to the mutual funds 3% of their profits through an important financing tool that is the solidarity funds (Fondi Mutualistici in Italian). These funds are then collected to reinvest into the creation of new cooperatives and similar projects, a possibility absent for other forms of enterprises.…”
Section: Cooperative Enterprises and Environmental Sustainabilitymentioning
confidence: 94%
See 1 more Smart Citation
“…They were suffering from the results of the Industrial Revolution with low pay, unhealthy cities, and dangerous workplaces resulting in a cooperative existing through mutual self-help. A sense of mutual help has been observed also in other countries, such as Italy, where according to the Law 59 (1992) [40] all cooperatives must transfer to the mutual funds 3% of their profits through an important financing tool that is the solidarity funds (Fondi Mutualistici in Italian). These funds are then collected to reinvest into the creation of new cooperatives and similar projects, a possibility absent for other forms of enterprises.…”
Section: Cooperative Enterprises and Environmental Sustainabilitymentioning
confidence: 94%
“…In their research on solidarity funds and comparative comparing scenarios from Italy, United Kingdom, and France, Bernardi et al (2022) [40] highlighted a crucial policy implication. They identified the necessity to establish dedicated institutions in countries where cooperatives are lagging behind.…”
Section: Cooperative Enterprises and Environmental Sustainabilitymentioning
confidence: 99%
“…Stakeholder consultations confirmed that one benefit of creating a specific legal form for social enterprises in Slovakia was enabling their access to European Social Funds (OECD, 2022 [2]). Another example is Canada that has created a Social Finance Fund in 2018 which is designed in such way that it can support SSE entities regardless of their activities (Sousa, 2021 [70]). This is an advantage as most grants, subsidies or other finance initiatives are focused on a specific policy objective (e.g.…”
Section: Facilitate Access To Funding and Financementioning
confidence: 99%
“…Longer life-spans and higher rates of activity are associated with membership to a cooperative association. It is thanks to them that workers can find expert guidance in the WBO process, which is not simple from a business, legal and financial point of view (Bernardi et al, 2022). To some extent, this is a case where cooperatives are better equipped than traditional firms.…”
Section: Entrepreneurship and Sustainability Issuesmentioning
confidence: 99%